Chronic pancreatitis caused by a Homozygous SPINK1 c.194 + 2T > C variant and Pancreas Divisum in a 3-year-old child—case report - Zdanowicz, Katarzyna; Uscinowicz, Miroslawa; Rakowska, Magdalena; Wertheim-Tysarowska, Katarzyna; Rygiel, Agnieszka Magdalena; Oracz, Grzegorz; Lebensztejn, Dariusz Marek (Journal of Pediatric Genetics, 2020)
Chronic pancreatitis (CP) is a rare disease in children. We describe the first case of a 3-year-old Caucasian patient with CP with the presence of a homozygous pathogenic variant c.194 + 2T > C in serine protease inhibitor, Kazal type 1 (SPINK1) and pancreas divisum.
Keywords: SPINK1; pancreas divisum; children